2022
DOI: 10.1039/d1tb01449h
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular cryoprotectants for the preservation of mammalian cell culture: lessons from crowding, overview and perspectives

Abstract: Cryopreservation is a process used for the storage of mammalian cells at a very low temperature, in a state of ‘suspended animation’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 152 publications
0
21
0
Order By: Relevance
“…26,28 Thus, it was also important to provide suitable extracellular membrane stabilization from macromolecular cryoprotectants. 3,31 It was reported that polyampholyte and sodium hyaluronate could synergistically enhance cryopreservation of sheep erythrocytes in mixed cryoprotectant systems with dimethyl sulfoxide and glycerol, respectively. 32,33 In addition to inhibiting ice recrystallization, the capability of cryoprotectants to stabilize cell membranes should be considered to increase the cryosurvival of human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…26,28 Thus, it was also important to provide suitable extracellular membrane stabilization from macromolecular cryoprotectants. 3,31 It was reported that polyampholyte and sodium hyaluronate could synergistically enhance cryopreservation of sheep erythrocytes in mixed cryoprotectant systems with dimethyl sulfoxide and glycerol, respectively. 32,33 In addition to inhibiting ice recrystallization, the capability of cryoprotectants to stabilize cell membranes should be considered to increase the cryosurvival of human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, the major challenges in cryopreservation technology are ice crystal formation, growth and recrystallization, which result in fatal cryoinjuries to biological samples. 3,4 Until now, flourishing cryoprotectants (CPAs) 5 have been developed quickly in cryobiology to inhibit ice recrystallization, shape ice crystals and depress the freezing point, such as glycerol, polyvinyl pyrrolidone, ethylene glycol (EG), propylene glycol (PG), dimethyl sulfoxide (DMSO), carbohydrates, AF(G)P and its mimics, trehalose, polyvinyl alcohol (PVA), polyampholytes, hydrogels, oxide graphite, proline, L-proline oligomers, MOFs, graphene oxide, 6 oxidized quasi-carbon nitride quantum dots, 7 and so on. However, DMSO is still the most common and gold-standard cryoprotectant, 8 showing a better protective effect in the media of cells for cryopreservation.…”
mentioning
confidence: 99%
“…As a result, there is a growing need to develop novel CPAs for cryopreservation that will minimize or obviate the use of DMSO. 5 Polyol and its analogues 5 (glycerol, EG, PG, carbohydrates, AF(G)Ps, trehalose and PVA), have been widely explored as alternative CPAs. In view of the structural characteristics of polyol-based CPAs, we surmise that cyclodextrins and crown ethers will have potential cryopreservation effects as antifreezing materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations